ANALISIS IMPLEMENTASI KURIKULUM 2013 PADA MATA PELAJARAN FISIKA DARI SEGI GURU SMA NEGERI PEKANBARU - Irdayasa, Dina Trisia; Irianti, Mitri; ', Azhar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aimed to describe the achievement level of curriculum 2013 implementation’s in Physics learning in term of the senior high school teachers Pekanbaru. This study is descriptive qualitative using survey method. A total of fifteen physics teachers from four senior high schools as parent cluster of curriculum 2013 in Pekanbaru has contributed in the process of collecting data by questioner. The data were analyzed by descriptive qualitative used to describe qualitative ordinal data such as achievement score implementation of curriculum 2013, which obtained from the research.The result showed that the achievement level of implementation curricullum 2013 in Physics Learning in term of the Senior High School teachers Pekanbaru included of the category quite well. Therefore, implementation of Curruculum 2013 has not done optimally yet.Key Words: Implementation of Curriculum 2013, Physics Learning, and Teachers